Effectiveness of antiseizure medications therapy in preventing seizures in brain injury patients: A network meta-analysis - Huo, Xianhao; Xu, Xingguo; Li, Mei; Xiao, Lifei; Wang, Yangyang; Li, Wenchao; Wang, Chaofan; Sun, Tao (Frontiers in Pharmacology, 2022)
Purpose: To explore the effectiveness of different antiepileptic drugs in preventing early and late post-traumatic epilepsy (PTE) after traumatic brain injury (TBI). The efficacy, treatment-related side-effects, and mortality of the different treatments were compared using a ranking model to identify the optimal treatment. Methods: A comprehensive literature search was performed using Pubmed, Medline, Embase, and Cochrane library. All relevant published articles up to March 10, 2022 were evaluated. The quality of the extracted data was assessed using either the Cochrane risk of bias tool or the Newcastle-Ottawa scale. The outcome measures were early or late PTE, mortality, treatment-related adverse effects, length of hospital stay, and length of stay within the ICU. Results: A total of 7 RCTs and 18 non-RCTs were included in this network meta-analysis. The trials included 6 interventions: PHT+ PB, LEV, PHT, PHT-LEV, LCM, and VPA. All interventions except VPA significantly reduced the rate of early PTE in TBI patients compared with placebo. Seven studies reported the impact of 4 treatments (PHT+PB, LEV, PHT, VPA) on late seizures and showed a significant reduction in the incidence of late seizures in patients with TBI compared with placebo. The impact of PHT, LEV, and VPA on mortality was reported in 9 studies. PHT had no impact on mortality, but patients treated with both LEV and VPA had higher mortality than those treated with placebo. The treatment-related adverse effects of LEV, PHT, and LCM were reported in 5 studies. LEV and PHT had higher treatment-related adverse effects incidence than placebo, while LCM had no effect on treatment related-adverse effects. Conclusions: LEV and PHT prevented early and late PTE in patients with TBI. PHT also reduced the mortality in patients with TBI. Both LEV and PHT had higher treatment-related adverse effects compared with placebo. However, LEV had a slightly lower incidence of treatment-related adverse effects when compared with PHT. Compared with PHT, LEV did not reduce the length of hospital stay but shortened the length of ICU stays. Therefore, we speculate that LEV is the best treatment option for TBI patients. However, further high-quality RCTs are required to confirm these findings.